Conditional Mutation of Rb Causes Cell Cycle Defects without Apoptosis in the Central Nervous System - MacPherson, D. (American Society for Microbiology, 2003)
Targeted disruption of the retinoblastoma gene in mice leads to embryonic lethality in midgestation accompanied by defective erythropoiesis. Rb(−/−) embryos also exhibit inappropriate cell cycle activity and apoptosis in the central nervous system (CNS), peripheral nervous system (PNS), and ocular lens. Loss of p53 can prevent the apoptosis in the CNS and lens; however, the specific signals leading to p53 activation have not been determined. Here we test the hypothesis that hypoxia caused by defective erythropoiesis in Rb-null embryos contributes to p53-dependent apoptosis. We show evidence of hypoxia in CNS tissue from Rb(−/−) embryos. The Cre-loxP system was then used to generate embryos in which Rb was deleted in the CNS, PNS and lens, in the presence of normal erythropoiesis. In contrast to the massive CNS apoptosis in Rb-null embryos at embryonic day 13.5 (E13.5), conditional mutants did not have elevated apoptosis in this tissue. There was still significant apoptosis in the PNS and lens, however. Rb(−/−) cells in the CNS, PNS, and lens underwent inappropriate S-phase entry in the conditional mutants at E13.5. By E18.5, conditional mutants had increased brain size and weight as well as defects in skeletal muscle development. These data support a model in which hypoxia is a necessary cofactor in the death of CNS neurons in the developing Rb mutant embryo.